Re-imagining contested communities connecting Rotherham through research - Campbell, Elizabeth 1962-; Pahl, Kate 1962-; Pente, Elizabeth ca. 20./21. Jh; Rasool, Zanib (Connected communities (Bristol, England), 2018)
Using history, artistic practice, writing, poetry, autobiography and collaborative ethnography, this book literally and figuratively re-imagines a place, presenting a 'how to' for researchers interested in community collaborative research and accessing alternative ways of knowing and voices in marginalised communities